DETERMINATION OF PERIOD OF THE FURNACE HEAPING BY MEANS OF AMPLITUDE OF ODD HARMONICS OF THE ARC PRESSURE - A. I. Rozhkov; V. V. Korotkevich (Литьë и металлургия)
The harmonic components of the arc pressure are investigated on blast steel furnace-1,2. The period of the furnace heaping by means of amplitude of odd harmonics of the arc pressure is determined.